Positive Zakat, Firm Size and Negative Leverage on BUS Performance: Zakat Positif, Firm Size dan Leverage Negatif terhadap Kinerja BUS - Indi Kaeza Zulfa; Amirah Amirah; Agus Prasetyono (Academia Open, 2025)
General Background: The growth of Islamic banking in Indonesia aligns with the country’s Muslim majority and is supported by legal frameworks promoting ethical finance. Specific Background: However, the performance of Islamic Commercial Banks (BUS) fluctuated from 2019 to 2024, warranting deeper investigation into its determinants. Knowledge Gap: Prior studies show inconsistent findings on the effects of zakat, Islamic Corporate Social Responsibility (ICSR), Sharia Supervisory Board Meetings (RDPS), firm size, and leverage on bank performance, revealing a gap in comprehensive analysis. Aims: This study aims to examine the simultaneous and partial influence of those five variables on BUS performance. Results: Using a quantitative method with SPSS 25 and multiple linear regression, the study finds that zakat has a significant positive effect, while firm size and leverage have significant negative effects on performance. ICSR and RDPS show no significant impact. The model explains 90.1% of the variance in ROA. Novelty: The integration of zakat as a strategic signal variable within the Sharia Enterprise and signal theory framework is a distinct contribution. Implications: Findings suggest the need for strategic zakat management, enhanced ICSR execution, stronger DPS governance, and optimized capital structures to improve BUS sustainability and competitiveness.Highlight : Zakat positively and significantly affects the performance of Islamic Commercial Banks (BUS) in Indonesia from 2019–2024. Firm size and leverage have a significant negative effect on BUS performance, indicating inefficiency and risk issues. ICSR and RDPS do not significantly influence performance, suggesting a gap in implementation or impact measurement. Keywords : Zakat, ICSR, RDPS, Firm Size, Leverage